(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This article determines the main quality indicators of Karakul pelts from Karakalpak Sur sheep in Shabdar and Chakir colors, specifically their luster and silkiness across different color variations, and provides conclusions for breeding.